Consumer preferences for innovative and traditional last-mile parcel delivery. Issue 3 (15th February 2022) - Merkert, Rico; Bliemer, Michiel C.J.; Fayyaz, Muhammad
Abstract : Purpose: The purpose of this research is to reveal consumer preferences towards innovative last-mile parcel delivery and more specifically unmanned aerial delivery drones, in comparison to traditional postal delivery (postie) and the recent rise of parcel lockers in Australia. The authors investigate competitive priorities and willingness to pay for key attributes of parcel delivery (mode, speed, method and time window), the role of contextual moderators such as parcel value and security and opportunities for logistics service providers in the growing e-commerce market. Design/methodology/approach: A survey involving stated choice experiments has been conducted among 709 respondents in urban Australia. The authors estimated panel error component logit models, derived consumer priorities and deployed 576 Monte Carlo simulations to forecast potential delivery mode market shares. Findings: The study results suggest that people prefer postie over drone delivery, all else equal, but that drone deliveries become competitive with large market shares if they live up to the premise that they can deliver faster and cheaper. Both drone and postie become less attractive relative to parcel lockers when there is no safe place to leave a parcel at a residence, highlighting the importance of situational context and infrastructure at the receiving end of last-mile delivery. The authors identified opportunities for chargeable add-on services, such as signature for postie and 2-h parcel deliveries for drones. Originality/value: The authors offer timely and novel insights into consumers preferences towards aerial drone parcel deliveries compared to postie and lockers. Going beyond the extant engineering/operations research literature, the authors provide a starting point and add new dimensions/moderators for last-mile parcel delivery choice analysis and empirical evidence of market potential and competitive attributes of innovative versus traditional parcel delivery alternatives.